SURVEI KONDISI FISIK DAN KETERAMPILAN TEKNIK DASAR BOLA VOLI PADA ANAK USIA DINI (9-11) TAHUN DI KLUB BOLA VOLI PUTRI WAHANA UTAMA PURWODADI TAHUN 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
Study aimed to determine the physical condition of the basic techniques and skills of volleyball in children aged ( 9-11 ) years in club Wahana Utama volleyball daughter. This research is descriptive quantitative approach. The sampling technique used was purposive sampling. The method used in this study is a survey of testing techniques and methods of data analysis using descriptive data analysis. Based on the survey results revealed that the physical condition of children aged ( 9-11 ) years in women's volleyball club Wahana Utama Purwodadi 15 % is included in the category of less, 60 % are moderate and 25 % is included in both categories. The level of ability of the basic techniques of volleyball in early childhood ( 9-11 ) years in women's volleyball club Wahana Utama Purwodadi for passing over 100 % in both categories once , passing under the category of either 20 %, 80 % very well, 35 % in service less category, 65 % medium category, smashes 15 % in the category of less, 25 % moderate category, 25 % good category, 35 % in both categories once. The conclusions of the study is the physical condition of the average child in the criteria being the basic techniques and skills in the poor category.